Hemoglobin Levels before and after Chemotherapy (Cisplatin-Paclitaxel) of Nasopharyngeal Cancer Patients at Prof. Dr. Margono Soekarjo Hospital (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: The National Comprehensive Cancer Network recommends induction chemotherapy and concurrent chemoradiotherapy as one of the standard therapy for stage II-IVA nasopharyngeal cancer. The use of induction chemotherapy given before radiotherapy is an effective treatment strategy because it has a better level of adherence and facilitates early eradication of micro metastasis. Chemotherapy has a direct side effect of disruption of erythrocyte formation in the bone marrow and reduces the erythropoietin hormone in the kidney. Decreased hemoglobin levels exacerbate oxygen deficiency in tumours thereby increasing hypoxic cells and contributing to the development of radiotherapy resistance. Objective: This research was conducted to find out the hemoglobin levels before and after chemotherapy (cisplatin-paclita An analytical observational studies with cross sectional method. The subjects were 36 nasopharyngeal cancer patients that gone through 6 cycles of chemotherapy and meets the research criteria.xel) in nasopharyngeal cancer patients. Methods: An analytical observational studies with  cross sectional method. The subjects were 36 nasopharyngeal cancer patients that gone through 6 cycles of chemotherapy and meets the research criteria. Results: The results of the bivariate analysis showed differences in the average of hemoglobin levels before and after chemotherapy, the average hemoglobin levels before chemotherapy which were 13.39 g/dL and after chemotherapy which were 11.35 g /dL in nasopharyngeal cancer patients at Prof. Dr. Margono Soekarjo Hospital (P=0,001). Conclusion: There is a significant difference between hemoglobin levels before and after chemotherapy (cisplatin-paclitaxel) in nasopharyngeal cancer patients in Prof. Dr. Margono Soekarjo Hospital.